PATIENT SAFETY CULTURE IMPROVEMENT TO ENHANCE THE QUALITY OF HEALTHCARE IN HARAPAN BUNDA HOSPITAL JAKARTA - Dilla, Hanifah Iskhia; Sulistiadi, Wachyu (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: One of the achievements in running health care service institutions (hospitals) is providing strategic health care services to improve health status. Harapan Bunda Hospital is a private hospital located in East Jakarta. Whose vision is to become the preferred hospital by providing the best quality service. One of the implemented programs was reporting incidents in the unit to the QPS Committee. However, the incident that occurred in Harapan Bunda Hospital is still not widely reported regularly by officers in the unit. In addition, there are many discrepancies in service delivery in the form of safety. Therefore, it is necessary to measure the Safety Culture at Harapan Bunda Hospital. Methods: This research used quantitative method with design cross sectional and used descriptive analysis to seek whole picture of all patient safety variable that had been done by Harapan Bunda Hospital. The population in this research is all staff of Harapan Bunda Hospital which around 708 staff member. Researcher used systematic random sampling with Slovin calculation formula and get 256 minimum sample needed. Instrument used is Patient Safety Culture survey refer to Agency for Healthcare Research and Quality (AHRQ). Results: The result of mean measurement patient safety culture in Harapan Bunda Hospital is 72%, it means Harapan Bunda Hospital was moderate Patient Safety Culture. There are dimensions being focused to improving patient safety culture; the overall perception of patient safety, feedback and communication about errors, communication openness, frequency of incident reporting, staffing and non-punitive responses to errors. Conclusion: Meanwhile, the other 6 dimensions of safety culture have been included in the good category of safety culture. Thus, Harapan Bunda Hospital is expected to always carry out routine monitoring and evaluation of the measurement of safety culture.